IDENTIFIKASI JENIS POLIMER MIKROPLASTIK PADA IKAN TONGKOL LISONG (Auxis rochei) DI PANTAI DAMAS PRIGI KABUPATEN TRENGGALEK JAWA TIMUR - Nindia Sukma Trivantira; Fitriyah Fitriyah; Mujahidin Ahmad (Binar – Biology Natural Resources Journal, 2023)
Plastic has a fairly wide distribution in human life. The use of microplastics is very difficult to avoid because it has reduced various human activities. The use of plastics on a large and wide scale raises a problem for the environment and ecosytem through the degradation of plastics into microplastics. Microplastics have the potential to pose a threat to the environment and organisms, especially in water areas. Their small size allows microplastics to be ingested by zooplankton up to a higher trophic level. Damas Beach is one of the marine tourism destinations in the Prigi bay area with a potential fishery sector in East Java. The high activity of tourism and fishing causes Damas beach to be potentially polluted by microplastics. This study aims to determine the type of plastic polymer in the digestive tract of lisong tuna obtained in the Damas beach area, Prigi Bay, Treanggalek Regency, East Java. This study used a purposive sampling method with two repetitions. Types of microplastic polymers were analyzed using FTIR. The results of the analysis showed that the types of plastic polymers found in the digestive tract of lisong tuna include High Density Polyethylene (HDPE), Polyvinyl chloride (PVC), nylon (polyamide, Polyethylene Terephthalate (PET), Polypropylene (PP), and Polystyrene (PS).